Frontispiece: Scanning‐Tunneling‐Spectroscopy‐Directed Design of Tailored Deep‐Blue Emitters. Issue 3 (12th January 2015) - Sanning, Jan; Ewen, Pascal R.; Stegemann, Linda; Schmidt, Judith; Daniliuc, Constantin G.; Koch, Tobias; Doltsinis, Nikos L.; Wegner, Daniel; Strassert, Cristian A.
<x xml:space="preserve">Abstract</x> Scanning Tunneling Spectroscopy D. Wegner, C. A. Strassert et al. describe in their Communication on page 786 ff. how scanning tunneling microscopy and spectroscopy can be used to visualize and measure the frontier orbitals of tridentate PtII complexes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>